Pemberdayaan Masyarakat melalui Pelatihan Pembuatan Tepung Sukun sebagai Bahan Baku Industri Rumah Tangga Desa Gunung Silanu - Ansar, Ansar; Mahi, Faizah; Syam, Agus Salim; Arfah, Aziza Noor Sheha; Hasan, Hasna (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Gunung Silanu Village has abundant potential for breadfruit harvests, but its utilization is still limited to the sale of raw fruit with low economic value. The main problems faced by partners are the rapid deterioration of the fruit after harvest and a lack of skills in food processing technology. This Community Service Program (PKM) activity aims to provide farmer groups and housewives with skills in processing breadfruit into flour. Methods used included outreach, hands-on training, and packaging assistance. The activity results showed an 80% increase in participants' understanding of the hygienic breadfruit flour production process. The resulting breadfruit flour has the potential to replace wheat flour as a raw material for local home industries, directly increasing the economic value of breadfruit and supporting food security in Gunung Silanu Village.